Trends in glycaemic control and drug use in males and females with type 2 diabetes: Results of the Australian National Diabetes Audit from 2013 to 2019. Issue 12 (23rd August 2021) - Xiang, Angie S.; Szwarcbard, Naomi; Gasevic, Danijela; Earnest, Arul; Pease, Anthony; Andrikopoulos, Sof; Wischer, Natalie; Davis, Wendy; Zoungas, Sophia
Abstract: Aim: To investigate temporal changes in glycaemic control and the use of antihyperglycaemic therapies in females and males with type 2 diabetes from 2013 to 2019. Methods: Data from adult patients with type 2 diabetes (n = 11 930; 44.9% females, mean [SD] age of 62.9 [12.9] years) were analysed from the 2013 to 2019 biennial cross‐sectional Australian National Diabetes Audit. Results: Mean HbA1c remained similar throughout the years examined and between the sexes (7.8%‐8.3%, 62‐67 mmol/mol; P  > .05). The number of antihyperglycaemic agents used by both sexes increased from 2013 to 2019 ( P  < .001), with more agents used by males ( P  = .014). From 2013 to 2019, there were increasing proportions of both sexes using dipeptidyl peptidase‐4 inhibitors (females: 11.7%‐25.7%, P  = .045; males: 11.6%‐29.5%, P  = .036) and glucagon‐like peptide‐1 receptor agonists (females: 5.9%‐15.3%; males: 4.9%‐11.1%; P  = .043 for both). Sodium‐glucose co‐transporter‐2 inhibitors were not available in 2013; however, their use increased substantially from 2015 to 2019 in both females (4.9%‐26.3%, P  = .013) and males (4.7%‐32.2%, P  = .019). Conclusions: From 2013 to 2019, mean HbA1c levels remained unchanged despite a concurrent increase in the number of antihyperglycaemic medications used. Overall, there was a trend towards preferencing newer agents with some differences in treatment regimens relating to sex and renal function.